Global Thrombosis Test – a possible monitoring system for the effects and safety of dabigatran. Issue 1 (December 2015) - Otsui, Kazunori; Gorog, Diana; Yamamoto, Junichiro; Yoshioka, Takayuki; Iwata, Sachiyo; Suzuki, Atsushi; Ozawa, Toru; Takei, Asumi; Inoue, Nobutaka
Abstract Background Dabigatran is an alternative to warfarin (WF) for the thromboprophylaxis of stroke in patients with non-valvular atrial fibrillation (NVAF). The advantage of dabigatran over WF is that monitoring is not required; however, a method to monitor the effect and the safety of dabigatran is not currently available. The Global Thrombosis Test (GTT) is a novel method to assess both clot formation and lysis activities under physiological conditions. Objective The aim of this study was to evaluate whether treatment with dabigatran might affect shear-induced thrombi (occlusion time [OT], sec) by the GTT, and to investigate the possibility that the GTT could be useful as a monitoring system for dabigatran. Patients/Methods The study population consisted of 50 volunteers and 43 NVAF patients on WF therapy, who were subsequently switched to dabigatran. Using the GTT, the thrombotic status was assessed one day before and 1 month after switching anticoagulation from WF to dabigatran. Results The OT was 524.9 ± 17.0 sec in volunteers whereas that of NVAF patients on WF therapy was 581.7 ± 26.3 sec. The switch from WF to dabigatran significantly prolonged OT (784.5 ± 19.3 sec). One patient on WF therapy and 12 patients on dabigatran therapy were shown to have OT > 900 sec. Conclusion The GTT could be used to assess the risk of dabigatran-related bleeding complications.